Implementasi Kedisiplinan Kerja di BKAD Kabupetan Gorontalo - R Nani, Novita Oktavyani; Sulila, Ismet; Mozin, Sri Yuliyanti (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to find out how work discipline is implemented at the Regional Financial and Asset Agency of Gorontalo Regency as seen from the aspects of 1) Punctuality of arrival at work, 2) Punctuality of time for returning home, 3) Compliance with applicable regulations, 4) Use of uniforms work, 5) Responsibility in carrying out tasks. The research method used in this research is a qualitative approach.The results obtained in this research show that the implementation of work discipline at the Gorontalo Regency Regional Financial and Asset Agency has been implemented well, however, there are still some employees who are not fully disciplined. Therefore, researchers provide some input in overcoming and resolving several deficiencies so that work discipline at the Gorontalo Regency Regional Financial and Asset Agency becomes more optimal in responding to delays that often occur.